2022
DOI: 10.3390/su14063194
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Farmers’ Awareness and Adoption of Extension Recommended Wheat Varieties in the Rainfed Areas of Pakistan

Abstract: Scientific evidence suggests that there is room for eradicating poverty and hunger by increasing food production through the adoption of modern agricultural practices by farmers. This study aimed, first, to explore the relationship between the farmers’ awareness and adoption of improved wheat varieties. Second, it aimed to find the key factors that govern the farmers’ awareness and adoption of extension-recommended innovations in the rainfed cropping system of the Khyber Pakhtunkhwa, Pakistan. Data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 73 publications
2
11
0
3
Order By: Relevance
“…Conversely, Ullah et al (2022) employed logistic regression to model farmers' innovation adoption decisions; they found education to negatively influence farmers' innovation adoption decisions in Pakistan. The importance of formal education on farmers' innovation adoption has given mixed results from past studies.…”
Section: Diffusion Of Innovation Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Ullah et al (2022) employed logistic regression to model farmers' innovation adoption decisions; they found education to negatively influence farmers' innovation adoption decisions in Pakistan. The importance of formal education on farmers' innovation adoption has given mixed results from past studies.…”
Section: Diffusion Of Innovation Theorymentioning
confidence: 99%
“…Rogers (2003) described innovators under the adopter category as young, rich, and educated, implying that age, income, and education play a crucial role in innovation adoption. However, research by (Ullah et al, 2022;Staddon 2020;Mwangi and Kariuki, 2015) found no relationship between one or more of these socioeconomic variable (age, income, education) and innovation adoption. Also, other studies on innovation adoption focused on a segment of the adopter categories, as can be found in (S€ a€ aksj€ arvi and Hell en, 2019;Vainauskas, 2003;Agarwal et al, 1998); also on the adoption of agricultural technology in small-scale farming, on a broader perspective (Atsriku, 2020), and on gender dimension of technology adoption (Quaye et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that awareness is a precursor to adoption. If the awareness of the technology is low, farmers are slow to adopt it (Fisher et al, 2018;Ullah et al, 2022). However, research on farmer perception of agricultural innovation and its role in adoption is scarce (Meshesha et al, 2022).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The farming community suffered during COVID-19: the timely purchase of modern agricultural inputs was prevented [ 15 ] and profitability was inhibited [ 16 ]. Along with COVID-19 restrictions that affected farmers’ markets integration, the farmers not only received inadequate extension services and faced imperfect inputs and outputs markets, but the poor infrastructure in rural areas prevented speedy adaptation to the circumstances [ 3 , 8 , 17 ]. Farmers, especially vegetable farmers, were affected by the disruptions to supplies of improved seeds and chemical fertilizers [ 2 ].…”
Section: Introductionmentioning
confidence: 99%